Treaty of Waitangi Principles Relevant to Adaptation to Coastal Hazards from Sea-Level Rise - Iorns, Catherine (Victoria University of Wellington Law Review, 2023)
This article addresses some duties that arise under Te Tiriti o Waitangi/the Treaty of Waitangi that are commonly referred to as "Treaty principles", and applies them to the new issue of protection of Māori interests in the face of coastal hazards associated with sea-level rise. It summarises the Māori interests likely to be affected by sea-level rise and related coastal hazards, and some adaptation measures. It summarises existing information on Crown duties under the Treaty of Waitangi with some comment on their application to local authorities. This includes a summary of the Treaty duties of the Crown (held by central government) and an explanation of how they are enforced. It outlines the Waitangi Tribunal decision on the MV Rena as an illustration of duties relevant to the handling of a disaster that damaged the coastal environment. It then discusses climate adaptation initiatives in the light of Treaty obligations, suggesting what Treaty principles might require of decision-makers and decision-making on climate adaptation measures under current law. While the focus of this article is limited to what existing law on the Treaty principles might require of government, it also briefly addresses recent developments that might expand legal obligations in the future. While this article stems from a project addressing adaptation to coastal hazards from sea-level rise, these findings and principles will be relevant to all climate adaptation decision-making, such as in relation to handling future floods and droughts.